Pengaruh Struktur Modal, Kualitas Audit dan Kepemilikan Manajerial terhadap Kualitas Laba - Indraswari, Putu Sri Widya Maretha; Werastuti, Desak Nyoman Sri (Universitas Pendidikan Ganesha, 2025)
This study aims to determine the effect of capital structure, audit quality, and managerial ownership on earnings quality. This study uses a quantitative approach with a causal associative research type. The data source for this study is secondary data, namely the annual financial reports of transportation and logistics sector companies from 2021 to 2024. The population of this study consists of 37 transportation and logistics sector companies listed on the Indonesia Stock Exchange. The research sample was selected using the purposive sampling method, meaning the selection of samples with certain criteria, resulting in a research sample of 56. The data obtained were then tested using IBM SPSS software version 27. The results of this study indicate that capital structure has a positive and significant effect on earnings quality. Audit quality has a negative and significant effect on earnings quality. Managerial ownership does not have a significant effect on earnings quality.